Knowledge, attitudes, and practices toward COVID-19 and its prevention among medical and dental students in an educational institution in Telangana - Preeti U. Deshpande; Anuradha Basavaraju; Nagapraveen Veerapu; Ashish Akula (Indian Journal of Pathology and Microbiology)
Background: Coronavirus disease 2019 (COVID-19) emerged as a global pandemic, threatening millions of lives worldwide. Everyone was overwhelmed by the plethora of information from different sources, creating confusion, misconceptions, and panic in the community. Aims: This study aimed to estimate the knowledge, attitudes, and practices (KAP) among medical and dental students toward COVID-19 and to identify factors influencing them. Materials and Methods: A cross-sectional study was conducted among undergraduate students enrolled in MBBS and BDS courses, and KAP scores were calculated using a self-administered questionnaire. The statistical analysis was done by unpaired t test and one-way analysis of variance. Results: MBBS students had higher KAP scores when compared with BDS students. Knowledge gaps were discovered in the areas of COVID-19 transmission through blood, World Health Organization (WHO)-designated variants of concern, disinfectant usage, and mandatory vaccination. A majority (91.33%) of the students had a positive attitude toward COVID-19. Better knowledge and practice scores were significantly associated with vaccinated students and those who trusted government website resources. Conclusion: Curriculum modifications and creative teaching strategies can fill the lacunae in the KAP scores. Medical and dental students, as torchbearers of the healthcare fraternity, can play a critical role in raising awareness during public health emergencies.